EFFECT OF ADDITION OF DIFFERENT LEVELS OF FORMIC ACID AND UREA ON CHEMICAL COMPOSITION AND FERMENTATION CHARACTERISTICS OF WILD REED PHRAGMITIS COMMUNIS SILAGE - & et al., Saeed (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2019)
This study was carried out in the laboratory to investigate the effect of addition of different levels of formic acid (FA) and urea on chemical composition and fermentation characteristics of common reed silages. About 400-500g of silage samples were prepared by treating chopped reed plants (2-3 cm) with solutions containing 10% of date juice, 0.5, 1 or 1.5% of FM and 0, 1 or 2% of urea. Silage samples were packed in double nylon bags and stored anaerobically for 60 days. Results showed that green color was roughly dominant in most samples of silage with vinegar odor. Samples were well aggregated with little mold was observed in few urea untreated silages. Results revealed also that increasing level of FA from 0.5 to 1 and 1.5% increased (P˂0.01) contents of dry matter (DM) by 0.79 and 1.15%, and crude protein (CP) by 1.42 and 2.11% respectively, and decreased (P˂0.01) ether extract (EE), by 0.29 and 0.63%. About effect of urea levels, most variables pointed out that there was a decrease may be occurred in fermentations due to a significant decrease in contents of DM (P˂0.01) and EE (P˂0.05). Content of crude fiber (CF) was decreased (P˂0.01) from 44.7 to 43 and 41.1% for 0, 1and 2% levels of urea respectively. Results showed that there was a decrease (P˂0.01) in pH values from 5.90 to 4.99 and 4.88, concentrations of ammonia nitrogen (NH3-N), from 1.19 to 0.75 and 0.66% of total nitrogen and total volatile fatty acids (TVFA) from 6.56 to 4.61 and 4.14 mmol/100 g DM of silage samples as a result of addition of FA at levels of 0.5, 1 and 1.5% respectively. However, increasing urea levels from 0 to 1 and 2% associated with an increase (P˂0.01) in fermentation parameters, 5.02, 5.06 and 5.70 for pH, 0.67, 0.98 and 0.95 for NH3-N and 3.70, 5.53 and 6.07 mmol/100 g DM for TVFA respectively